The trend of mobile malwares and effective detection techniques - Abdul Aziz, Normaziah; Adebayo, Surajudeen Adebayo (IGI-Global, 2015)

(untitled)
The usefulness of mobile phones nowadays has gone beyond making calls and sending text messages. In fact, most of applications available on desktop computer are presently easily accessible on mobile devices, especially smartphone based on Androids, iOS, and Windows phone platforms. However, at the same time, malware is increasingly becoming pervasive on a mobile platform for financial, social and political exploitation. This chapter examines the trends of mobile malware and different efforts of anti-malware writers and researchers in addressing mobile malware on smartphones. Chapter Preview